Early Warning Signs in Software Projects - Kothari, Mihir (Auckland University of Technology, 2010)
The software industry has been plagued by the staggering failure rate of projects, which have resulted in the loss of billions of dollars. The well known Chaos Report by the Standish Group declared that software projects are in chaos with only 16.2% of software projects actually being successful in the year 1994 and a more recent study by them suggest that 32% of the projects were successful in the year 2009 (Eveleens and Verhoef, 2010; Dominguez, 2009; Bishop, 2009). The post-mortem examination of failed software development projects reveals that failures do not happen overnight and that long before the failure, the projects render significant symptoms or “early warning signs” of trouble (Kappelman, McKeeman and Zhang, 2006). A warning sign is an indication or an event that predicts or alerts impending problems. Early warning sign provide an indication of manifesting risks. This research mainly focuses on a new and innovative concept known as early warning signs which could be incorporated into ongoing project risk management to ameliorate the project success rates by addressing early warning signs encountered during the project. The project risk management theories are not closely integrated with the early warning phenomenon but this can apparently be utilised as a tool in project risk management (Nikander, 2002). The study utilises the System Development Research Methodology. The models simulating a typical project environment were designed using a simulation tool known as SimSE. For the evaluation of the models two experimental techniques namely “Individual EWS Testing” and “Controlled Experimental Study” were used. Findings of the research suggest that the implementation of early warning phenomenon has positive effects on the project outcomes. Also, there is a positive impact on the project outcomes if the corrective actions are taken early. The concept of early warning signs looks promising and this study is just one step in this direction and has introduced this new concept to the research arena.
Keywords: Project Management; Software development projects; Early warning signs in Software Projects; IT Projects; System Development Research Methodology (SDRM); Simulation; Controlled experimental study; Software Project failures; Uncertainty in Software Projects; Risk Management; Proactive Risk Management